2009
DOI: 10.1017/s1368980009991595
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the availability and accessibility of healthy food in rural and urban New Zealand – Te Wai o Rona: Diabetes Prevention Strategy

Abstract: Objective: Uptake of advice for lifestyle change for obesity and diabetes prevention requires access to affordable 'healthy' foods (high in fibre/low in sugar and fat). The present study aimed to examine the availability and accessibility of 'healthy' foods in rural and urban New Zealand. Design: We identified and visited ('mapped') 1230 food outlets (473 urban, 757 rural) across the Waikato/Lakes areas (162 census areas within twelve regions) in New Zealand, where the Te Wai O Rona: Diabetes Prevention Strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Some countries, for example Brazil, are now using guidelines as an opportunity to promote the health and well-being of people, an avenue which may garner broad appeal, especially across multiple ethnic groups [29]. Availability and accessibility of healthy food varies [30], as does food security between families based upon their household deprivation and ethnicity. These factors need to be taken into account in any attempt to address eating behaviours in the obese child and adolescent population [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some countries, for example Brazil, are now using guidelines as an opportunity to promote the health and well-being of people, an avenue which may garner broad appeal, especially across multiple ethnic groups [29]. Availability and accessibility of healthy food varies [30], as does food security between families based upon their household deprivation and ethnicity. These factors need to be taken into account in any attempt to address eating behaviours in the obese child and adolescent population [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Liese et al, (2007) discovered that the availability of healthy food was substantially higher in supermarkets in comparison to independent stores. Hence, Wang et al (2010) found that healthy food was more readily available in urban than in rural environments (Wang et al, 2010). There is also a price penalty with healthy produce costing approximately one-third more in rural environments (Shaw, 2014).…”
Section: Urban-rural Negative Health Gradientmentioning
confidence: 99%
“…While current research focuses on associations between food prices at the regional, city and neighborhood levels and food consumption behaviors and patterns, [ 17 22 ] examining the monetary value of the diet (MVD) and how it is related to various dietary components and quality has gained more recent interest. [ 10 , 23 53 ] Most studies reported a direct relationship between MVD and diet quality (or an inverse relationship with consumption of energy-dense foods),[ 10 , 23 31 , 33 38 , 40 42 , 44 47 , 50 , 51 , 54 60 ], a finding not replicated in other studies. [ 32 , 39 , 43 , 48 , 49 ]…”
Section: Introductionmentioning
confidence: 98%